2020
DOI: 10.1186/s41938-020-00218-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Bacillus thuringiensis isolate-based formulation against the pod borer, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae)

Abstract: The present study focuses on the evaluation of the potential of a Tunisian Bacillus thuringiensis (Bt) isolate named Hr1, isolated from dead and diseased pod borer, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) larvae under laboratory and field semi-controlled conditions. The bacterial strain Hr1 showed an insecticidal activity against the pest's neonates in comparison to the spinosad-based insecticide (Tracer 240 SC®) during bioassays under laboratory conditions. A carboxymethyl cellulose-talc (CMC-tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Taxonomic classification of these toxins placed themes in the delta category of insect toxins because of their intracellular position (Schnepf et al 1998). Crystalline toxins or δ-endotoxins are considered the main factor conferring entomopathogenic properties to Bt (Bouslama et al 2020). δ-endotoxins are composed of 74 types of toxins and holotypes of 295 that belong to the 3D protein family synthesized by Bt (Leopoldo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic classification of these toxins placed themes in the delta category of insect toxins because of their intracellular position (Schnepf et al 1998). Crystalline toxins or δ-endotoxins are considered the main factor conferring entomopathogenic properties to Bt (Bouslama et al 2020). δ-endotoxins are composed of 74 types of toxins and holotypes of 295 that belong to the 3D protein family synthesized by Bt (Leopoldo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Highest number of these pests was recorded in the untreated plot. The toxicity of B. thuringiensis on tomato pests has been reported by many authors amongst which Thameur et al (2020) [21] , in the control of H. armigera a pests of tomato in India and also by Shahini et al (2021) [19] in the control of T. absoluta in Albania, Mediterranean basin. Shaukat et al (2010) [20] confirmed the efficacy of B. thuringiensis on many other crop pests.…”
Section: Discussionmentioning
confidence: 93%
“…The obtained data were in conformity with other several studies that have proven the toxicity of different strain of Bt against some insects as Bt var. thuringiensis against the cotton leaf roller, Syllepte derogata (Gahramanova et al, 2020), Bacillus thuringiensis CAB109 on Spodoptera exigua (Huang et al, 2018), Bt against the pod borer, Helicoverpa armigera (Bouslama et al, 2020;Fite et al, 2019), Bt against P. gossypiella (Abbas et al, 2017). The LC50 values for Bt 4D1, Bt 4D4 and Bt 4G1 were 6.10, 6.62 and 8.18 μg/ml for the 2nd instar; 9.90, 10.20 and 11.12 μg/ml for the 3rd instar; and 19.82, 23.16 and 24.54 μg/ml for the 4th instar, respectively, while the Bt 4K5 and Bt 4XX4 were not toxic to Tuta absoluta (Sandeep Kumar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%